Marx y los fundamentos crítico-filosóficos de la esfera pública - Jurado-Castaño, Pedro Alejandro; Tobón-Velásquez, Sebastián (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2022)
This paper presents the presuppositions that enable a critical reflection on the public sphere from a Marxist perspective. It begins by considering the contextof recent discussions concerning Marx’s political ideas, and the relevance of the concept of public sphere in order to show the importance of some of Marx’s critical concepts for political philosophy. The text is the result of a research project aimed at constructing a conceptual framework to develop a critical analysis of the public sphere today. This research has already established that some key issues, linked to the concepts of language and experience, were present in Marx’s work. In this sense, the paper presents a novel reflection to the extent that it deals with the actuality of Marx’s thought through the analysis of a contemporary political problem that allows to highlight the critical and radical implications that Marx’s philosophical-critical foundations have for contemporary discourse and politicalinstitutions such as the public sphere.

En este artículo exponemos los presupuestos que permiten una reflexión crítica sobre la esfera pública desde una perspectiva marxista. Hemos partido de laconsideración del contexto de discusión reciente sobre las ideas políticas de Marx y de la relevancia del concepto de esfera pública para mostrar la importancia de algunos de sus conceptos críticos para la filosofía política. El texto es producto de una investigación dedicada a la elaboración de un marco conceptual que persigue el desarrollo de un análisis crítico de la esfera pública en la actualidad y en el que se ha establecido que algunas cuestiones claves, vinculadas a los conceptos de lenguaje y experiencia, se encontraban presentes en la obra de Marx. En este sentido, el texto presenta una novedosa reflexión al tratar la actualidad del pensamiento de Marx desde el análisis de un problema político contemporáneo que permite poner en evidencia las implicaciones críticas y radicales que poseen sus fundamentos filosófico-críticos para los discursos y las instituciones políticas contemporáneas como la esfera pública.
Marx and the Critical-Philosophical Foundations of the Public Sphere
Keywords: Marx; Public sphere; Marxism; Language; Contemporary political philosophy; Marx; Esfera pública; Marxismo; Lenguaje; Filosofía política contemporánea; https://purl.org/pe-repo/ocde/ford#6.03.01